อนาคตของการออกแบบทางสถาปัตยกรรม การผสมผสานระหว่างมนุษย์และเทคโนโลยีในสื่อภาพเคลื่อนไหว - Nakmontanakum, Sasina (วารสารสถาปัตยกรรม การออกแบบและการก่อสร้าง, 2021)
This paper examines the evolution of the concept of the "future" from the 1920s to the 2020s. Science fiction moving picture media is an apparatus that connects the imaginative and physical worlds. The visionary work demonstrates how the world changes over time through architectural languages, human behaviour, and technological innovation. This thesis investigates technological science-fiction moving image media (film, television series, and documentaries) and associated architectural designs. It also aims to define and pattern the future, focusing on technological advancement and people's expectations for the future across time. The study demonstrates the relationship between moving-picture media (Sci-Fi genre), associated architectural designs, historical event influences, and technological progress. The main points to focus on are the evolution of habitation, transportation, communication, identification, automation, and consumption.